2016
DOI: 10.3390/molecules22010054
|View full text |Cite
|
Sign up to set email alerts
|

A New Determination Method of the Solubility Parameter of Polymer Based on AIE

Abstract: An accurate method of the fluorescence probe approach based on an aggregation-induced emission (AIE) molecule (tetraphenylethylene) for measuring the solubility parameter of the polymer is reported. This method is distinctive in that the approach can make the polymer chain conformation in solution be related to the fluorescence intensity. Since the solubility parameter of the polymer is also closely linked to its chain conformation in solution, the solubility parameter can be determined by the fluorescence int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Our preliminary investigations into the RAFT polymerization of A‐TPE‐Br using different chain transfer agents (dithiobenzoate‐, trithiocarbonate‐ and xanthate‐type mediating agents) and polymerization solvents suggested that 2‐cyano‐2‐propyl dodecyl trithiocarbonate was an efficient RAFT agent, in terms of the low dispersity of the products with reasonable polymer yields, as shown in Table S1 and Figures S2 and S3 (SI). To our knowledge, this is the first report on the controlled RAFT polymerization of the brominated TPE‐containing acrylate (A‐TPE‐Br), although controlled and free radical (co)polymerizations of nonbrominated TPE‐containing (meth)acrylate has been reported by several groups 24–27,47–51 …”
Section: Resultsmentioning
confidence: 97%
“…Our preliminary investigations into the RAFT polymerization of A‐TPE‐Br using different chain transfer agents (dithiobenzoate‐, trithiocarbonate‐ and xanthate‐type mediating agents) and polymerization solvents suggested that 2‐cyano‐2‐propyl dodecyl trithiocarbonate was an efficient RAFT agent, in terms of the low dispersity of the products with reasonable polymer yields, as shown in Table S1 and Figures S2 and S3 (SI). To our knowledge, this is the first report on the controlled RAFT polymerization of the brominated TPE‐containing acrylate (A‐TPE‐Br), although controlled and free radical (co)polymerizations of nonbrominated TPE‐containing (meth)acrylate has been reported by several groups 24–27,47–51 …”
Section: Resultsmentioning
confidence: 97%
“…11B). 73 The d of the solvent, in which the polymer chains were in the fully stretched conformations, could serve as the d of the polymer itself. As shown in Fig.…”
Section: Physical Processesmentioning
confidence: 99%
“…Glycidyl methacrylate (GMA) has been widely used in the modification of polyolefin because of its characteristics of nontoxicity and high activity . Tetraphenylethylene can emit strong light in a solid state as a typical aggregation‐induced emission (AIE) effect, and this can be used in fluorescence labeling …”
Section: Introductionmentioning
confidence: 99%